Analisis Pengelolaan Dana Zakat Produktif Dalam Memberdayakan UMKM Pada Lazis Muhammadiyah (LAZISMU) Kabupaten Lamongan - Mahmudah, Latifatul; Yasin, Ach (Universitas Negeri Surabaya, 2022)
LAZISMU Lamongan Regency has a goal to assist the government in improving welfare and independence in the community. Since the year of its establishment until now, LAZISMU Lamongan Regency has an independent business program with the concept of providing business capital assistance to mustahiq. LAZISMU Lamongan Regency in implementing an independent business program by providing business assistance capital to MSME actors in Lamongan Regency who need additional funds for business capital. The purpose of this study is to see the zakat fund collection system carried out by LAZISMU Lamongan Regency and to find out the empowerment of MSMEs carried out by LAZISMU Lamongan Regency. Theiresearch methode used is descriptiveiqualitative. The resultsiof the study stated that the management of zakat in LAZISMU, Lamongan Regency was in accordance with sharia principles. Fundraising is done through two systems, namely direct and indirect. Zakat funds that have been collected will then be distributed according to asnaf. Management of zakat funds uses management principles, namely planning, organizing, mobilizing, and supervising. The distribution of zakat funds at LAZISMU Lamongan Regency is carried out using two types of distribution, namely traditional consumptive and creative productive. The empowerment carried out by LAZISMU in Lamongan Regency is in the form of counseling and mentoring with the aim of developing the knowledge and skills possessed.